Paraneoplastic Syndrome of Myasthenia Gravis Presenting as Isolated Vocal Cord Paralysis in a Patient with Breast Cancer: Case Report and Literature Review (Global Journal of Medical Research, 2023)
53-year-old lady presented with progressively worsening loss of voice Over time she could only be heard upon speaking directly into the ears of her family or physicians She lost her job as a receptionist due to her loss of voice She was still on adjuvant treatment for breast cancer She underwent CT PET ENT consultation and a battery of paraneoplastic antibody tests ENT consultation confirmed vocal cord paralysis ENT exam and CT PET found no evidence of vocal cord mass or any lesion compressing the laryngeal nerves No mass was found in the superior mediastinum She had a positive antibody test for anti-acetylcholine receptors Treatment with pyridostigmine reversed her vocal cord paralysis This is the first report of a patient with breast cancer associated paraneoplastic myasthenia gravis syndrome